Introduction to graph theory - West, Douglas B (New Delhi : PHI, 2001)
This text offers a comprehensive and coherent introduction to the fundamentals of graph theory. Written in a reader-friendly style and with features that enhance students' comprehension, the book focuses on the structure of graphs and techniques used to analyze problems. Greatly expanded and reorganized, this edition is integrated with key pedagogical aids like numerous illustrations, cross-references, and 'warm-up' exercises that provide for in-depth understanding of the topics covered in the text. Other important features of the book include multiple approaches towards problem solving and definitions following the use of concepts for meaningful distinction and clarity.
Appendix A-F 471-568p.; Author index 569-574p.; Subject index 575-588p.
Keywords: Planar graphs; Trees and distance; Ramsey theory